The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00792-017-0956-9
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights into temperature-dependent transcriptional responses of Kosmotoga olearia, a deep-biosphere bacterium that can grow from 20 to 79 °C

Abstract: Temperature is one of the defining parameters of an ecological niche. Most organisms thrive within a temperature range that rarely exceeds ~30 °C, but the deep subsurface bacterium Kosmotoga olearia can grow over a temperature range of 59 °C (20–79 °C). To identify genes correlated with this flexible phenotype, we compared transcriptomes of K. olearia cultures grown at its optimal 65 °C to those at 30, 40, and 77 °C. The temperature treatments affected expression of 573 of 2224 K. olearia genes. Notably, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 68 publications
(125 reference statements)
1
22
0
Order By: Relevance
“…3). Both genes were transcribed at moderate levels in M. prima grown with thiosulfate (RPKM 341 and 243 respectively), whereas the K. olearia homologues (Kole_1827, Kole_1828) were highly expressed under similar conditions (RPKM > 1000; Pollo et al, 2017). SudAB complexes, however, are not known to be involved in thiosulfate reduction.…”
Section: Distinct Metabolism In Mesophilic Thermotogaementioning
confidence: 99%
See 2 more Smart Citations
“…3). Both genes were transcribed at moderate levels in M. prima grown with thiosulfate (RPKM 341 and 243 respectively), whereas the K. olearia homologues (Kole_1827, Kole_1828) were highly expressed under similar conditions (RPKM > 1000; Pollo et al, 2017). SudAB complexes, however, are not known to be involved in thiosulfate reduction.…”
Section: Distinct Metabolism In Mesophilic Thermotogaementioning
confidence: 99%
“…Fadhlaoui et al (2017) suggested that Mesotoga's inability to ferment sugars is mainly due to its lack of a bifurcating hydrogenase. However, K. olearia also lacks this enzyme and ferments pyruvate, producing large amounts of hydrogen using the homologue of M. prima's only Fe-hydrogenase (Pollo et al, 2017). In the model in Fig.…”
Section: Distinct Metabolism In Mesophilic Thermotogaementioning
confidence: 99%
See 1 more Smart Citation
“…(Fadhlaoui 425 et al, 2017) suggested that Mesotoga's inability to ferment sugars is mainly due to its 426 lack of a bifurcating hydrogenase. However, K. olearia also lacks this enzyme and 427 ferments pyruvate, producing large amounts of hydrogen using the homolog of M. 428 prima's only Fe-hydrogenase (Pollo et al, 2017). In the model in Fig.…”
Section: Moreover the Us-lineage Has An Intermediate Position Betweementioning
confidence: 99%
“…534 Recombinant fragments between lineages were detected using LikeWind Version 1.0 535 (Archibald and Roger, 2002) on the concatenated MAUVE alignment (above), using a 536 sliding window of 1000 bp with 100-bp increments. 537 538 RNAseq analysis 539RNA isolation from a culture of M. prima (grown at 45ºC for 73 h in 0.5% yeast extract, 540 0.01 M thiosulfate and 0.5% xylose) and subsequent sequencing as one of five barcoded 541 libraries were performed as described by(Pollo et al, 2017). RNAseq analysis was 542 carried out in CLC Genomics Workbench version 7.0.4 as described by(Pollo et al, 543 2017).…”
mentioning
confidence: 99%